2014
DOI: 10.1016/j.plefa.2014.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E isoforms disrupt long-chain fatty acid distribution in the plasma, the liver and the adipose tissue of mice

Abstract: Evidences suggest that omega-3 fatty acid (n-3 PUFA) metabolism is imbalanced in apolipoprotein E epsilon 4 isoform carriers (APOE4). This study aimed to investigate APOE genotype-dependant modulation of FA profiles, protein and enzyme important to fatty acid (FA) metabolism in the adipose tissue, the liver and the plasma using human APOE-targeted replacement mouse-model (N=37). FA transport (FATP) and binding (FABP) protein levels in tissues and concentrations of liver carnitine palmitoyltransferase 1 (CPT1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 40 publications
3
15
0
Order By: Relevance
“…In line with this hypothesis, transgenic mice knock-in for the human APOE4 had higher FA transport proteins in the liver together with higher hepatic carnitine palmitoyl transferase 1 than did APOE3 mice (26). Carnitine palmitoyl transferase 1 is the rate-limiting enzyme for mitochondrial b-oxidation.…”
Section: Discussionmentioning
confidence: 66%
“…In line with this hypothesis, transgenic mice knock-in for the human APOE4 had higher FA transport proteins in the liver together with higher hepatic carnitine palmitoyl transferase 1 than did APOE3 mice (26). Carnitine palmitoyl transferase 1 is the rate-limiting enzyme for mitochondrial b-oxidation.…”
Section: Discussionmentioning
confidence: 66%
“…This is unlikely to be attributed to greater activity in these mice, as physical activity—although contributing to daily energy expenditure—has no effect on total energy expenditure in mice housed below their thermoneutrality ( 32 ). Two recent studies indicated that in mice, the APOE4 genotype is associated with an increased basal mitochondrial uncoupling and fatty acid oxidation compared to the APOE3 genotype ( 11 , 33 ). LC n-3 PUFAs increase mitochondrial biosynthesis and oxidative capacity, as well as fatty acid oxidation ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between dietary Challenges to determining whether DHA can protect against age-related cognitive decline Review and plasma DHA therefore seems to shift in carriers of APOE4, who need higher dietary fish intakes to increase plasma DHA concentration [60]. In carriers of APOE4, β-oxidation may preferentially affect omega-3 PUFA compared with monounsaturated or saturated fatty acids, explaining the modification of DHA metabolism occurring with APOE4 [96,97].…”
Section: Docosahexaenoic Acid Metabolism During Age-related Cognitivementioning
confidence: 99%